- #1

- 38

- 0

so i need to find a,b, and c:

(M^0)*(L^0)*(T^1) = (M^a+b+c)*(L^-a-3b+2c)*(T^-2a-2c)

to solve i equated the exponents to that of each matching variable:

a+b+c = 0

-a-3b+2c = 0

-2a-2c = 1

Is there a mathematical process of obtaining the above equations besides simply "equating" the exponents? Like taking the natural log or something like that?

(M^0)*(L^0)*(T^1) = (M^a+b+c)*(L^-a-3b+2c)*(T^-2a-2c)

to solve i equated the exponents to that of each matching variable:

a+b+c = 0

-a-3b+2c = 0

-2a-2c = 1

Is there a mathematical process of obtaining the above equations besides simply "equating" the exponents? Like taking the natural log or something like that?

Last edited: